THE IMAGE OF A WITCH: G. F. KVITKA-OSNOVYANENKO'S LITERARY VERSION - Danyliuk-Tereshchuk, T. Ya. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article reveals the functional peculiarities of the image of a witch in the folklore text and in the text created by an author. In the focus of the analysis is the story “Konotopska Witch” by G. F. Kvitka-Osnovianenko. For the first time in the national literature the writer has traced the way and the means of how popular beliefs or prejudices form the social consciousness. The witch's “might” of the main character gives the author an oportunity to deduce the way to the archetypal content of the image. This demonological character embodies the dark side of the female nature and exposes the attitude of a man to a woman, his fear of her power. The irrational power of the witch frightens and determines the incomprehensibility of the Otherness.